What Differences in the Cultural Backgrounds of Partners Are Detrimental for International Joint Ventures? - Barkema, Harry G.; Vermeulen, Freek (Journal of International Business Studies, 1997)
An international joint venture implies that a firm has to cooperate with a partner with a different cultural background. In this study, hypotheses about which differences in national culture are most disruptive for international joint ventures were developed and tested using Hofstede's five dimensions. The study focused on how these dimensions affect the survival of international joint ventures, as well as their incidence relative to wholly owned subsidiaries. The hypotheses were tested on longitudinal data about 828 foreign entries of twenty-five Dutch multinational in seventy-two countries between 1966 and 1994. The database, which spans almost three decades, was also used to provide new evidence on a key assumption of Hofstede's work: that cultural values are stable over time.